Digital Tunes of Indonesia: Investigating Likeability, Perceived Value and Behavior in Dangdut Music Streaming Platform - Muhammad Arief Asad; Tutur Wicaksono (STIE Pariwisata API Yogyakarta, 2026)
Dangdut music stands out as a favored genre among music enthusiasts in Indonesia. This study analyzes the influence of likeability, perceived value, and user behavior within the Indonesian dangdut music genre. Adopting an exploratory approach and surveyed 242 respondents who use music streaming applications that feature dangdut music content. The chosen analytical method was Structural Equation Model (SEM) analysis. The study's findings indicate that content attractiveness, perceived value, likeability, and intention play significant roles in shaping the behavior of users of Dangdut streaming music applications. Notably, likeability and perceived value impact both intention and behavior. The behavioral model constructed for the usage of streaming music applications integrates perceived value and likeability, reflecting a modified TAM-likeability-perceived value model. This study highlights the significant impact on the future of music streaming in Indonesia. The findings emphasize the importance of active participation in ensuring the continuous growth and improvement of the user experience in the dynamic digital music environment. Active engagement and participation in the music streaming industry are identified as key drivers of continuous growth and relevance. By actively involving users, the industry can adapt to the ever-evolving digital music landscape and ensure that the overall user experience remains enjoyable and resonant with the changing preferences and needs of the audience. This research sheds light on the critical interplay between user involvement and the future trajectory of music streaming services in Indonesia.